Distribution of Rare-Earth Elements in Ashes Produced in the Coal Combustion Process from Power Boilers - Zdzisław Adamczyk; Joanna Komorek; Magdalena Kokowska-Pawłowska; Jacek Nowak (Energies, 2023)
The growing demand for rare-earth elements and yttrium (REY) in modern technologies has resulted in the systematic depletion of primary ores. For this reason, research is being conducted around the world on alternative sources of rare-earth elements, e.g., on the possibilities of recovering REY from coal waste or coal combustion. The article presents the results of comprehensive tests of the fuel—hard coal, and high-temperature HTA ash, fly ash, and bottom ash. Examined samples were taken from a Polish power plant. In the tests, fuel quality parameters were determined in accordance with the standards; microscopic observations in reflected and transmitted light, as well as a scanning electron microscope (SEM/EDS), were used, and chemical and phase composition were determined using ICP-MS and XRD methods, respectively. The distribution of REY between these ashes was analyzed. Their suitability as alternative sources of REY was assessed. The obtained results showed that the process of hard coal combustion in pulverized coal boilers influenced the geochemical differentiation of REY elements in energy waste. This differentiation is manifested by higher concentrations of REY and critical elements in the fly ash than in the bottom ash. The obtained values of the Coutl prospective coefficient made it possible to classify the analyzed fly and bottom ashes as prospective REY raw materials.